Activity‐dependent dysfunctional gene expression patterns are normalized by in vivo treatment of late‐stage Aβ pathology mice with a TrkB/C small molecule ligand. (31st December 2021) - Latif‐Hernandez, Amira; Moran‐Losada, Patricia; Yang, Tao; Tran, Kevin C; Liu, Harry; Butler, Robert R.; Massa, Stephen M.; Longo, Frank M.
Abstract: Background: Neurotrophin signaling via TrkB and TrkC receptors participates in long‐term potentiation (LTP), a biological substrate of memory formation that is disrupted by amyloid‐β (Aβ) in APP mice. In this study, we ask whether there are alterations in activity‐dependent gene expression signatures in APP mice, and if so, could elements of these alterations be restored by prior treatment with a small molecule TrkB/C partial agonist, PTX‐BD10‐2. Method: We administered PTX‐BD10‐2 (50 mg/kg) or vehicle (VEH) orally once daily to male wild type (WT) and APP mice expressing London and Swedish mutations (APP‐L/S) for 3 months starting at 13 months of age. Paired‐pulse ratios (PPR) and Theta Burst Stimulation (TBS) were applied to acute hippocampal slices, in absence of drug, to induce short and long‐term synaptic plasticity. Upon completion of recordings, we examined whole tissue transcriptomic profiles for differential gene expression and enrichment of ontological terms and pathways. Result: Pronounced deficits in PPR (at 10 and 20 ms) and LTP were found in APP‐L/S relative to WT slices, and entirely restored in slices from APP‐L/S mice treated with PTX‐BD10‐2 (Fig. 1). To identify candidate mechanisms of this pre/post synaptic plasticity rescue, we examined activity (TBS)‐dependent transcriptomic signatures. Analysis of TBS‐only slices demonstrated alterations in gene expression between WT_VEH_TBS and APP‐L/S_VEH_TBS mice. In particular, significant downregulation of genes in pathways known to be important for synapse function: axoneme, glutamatergic/GABAergic synaptic signaling, neurotransmitter release/transmission and neuronal action potential ; and upregulation of gene pathways that are candidates contributing to degeneration in AD and in APP‐L/S_VEH_TBS mice: immune system processes, inflammatory responses, aging and neuron death; when compared to WT_VEH_TBS. Remarkably, the altered expression levels of most of the genes from these pathways were reverted to WT pattern in APP‐L/S_BD10‐2_TBS mice (Fig. 2), thus revealing candidate mechanisms to restore PPR and LTP deficits in APP‐L/S mice. Conclusion: PTX‐BD10‐2 treatment mitigates Aβ‐related synapse dysfunction and alterations in synapse‐relevant gene expression profiles in APP‐L/S mice in the context of stimulation. These findings point to therapeutic potential of targeting TrkB/C, and moreover, provide a cellular model to identify candidate signaling modules for understanding synaptic impairment and revealing novel therapeutic targets.